2019
DOI: 10.5539/hes.v9n1p86
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Individual and Interpersonal Level Factors Associated with Academic Success of College Students at a Women’s, Faith-based Higher Institution

Abstract: The present study investigated how spirituality, peer connections, and social integration relate to academic resiliency, academic self-efficacy, academic integration, and institutional commitment of college students who identify as female. A sample of 372 undergraduates (ages 18-26) at a Catholic University completed Mapworks survey containing institution-specific questions and spirituality items in Spring 2018. Pearson correlation was used to examine the bivariate relationships between the variables. Canonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The squared canonical correlation coefficients of .55, .24, and .04 for Functions 1, 2, and 3, respectively ( p s < .01), indicate that the commonality between SPS and the Big Five traits was about 55%, 24%, and 4% for each Function. Because the commonality between the two constructs was relatively low and most of the structured coefficients (i.e., correlation coefficients between a synthetic variable and an observed variable) were not noteworthy (| r s |s < .45; Ekwonye & DeLauer, 2019), it was difficult to interpret the Functions 2 and 3 results. However, Function 1 had acceptable structured coefficients for all the components except conscientiousness (| r s |s > .45; Ekwonye & DeLauer, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The squared canonical correlation coefficients of .55, .24, and .04 for Functions 1, 2, and 3, respectively ( p s < .01), indicate that the commonality between SPS and the Big Five traits was about 55%, 24%, and 4% for each Function. Because the commonality between the two constructs was relatively low and most of the structured coefficients (i.e., correlation coefficients between a synthetic variable and an observed variable) were not noteworthy (| r s |s < .45; Ekwonye & DeLauer, 2019), it was difficult to interpret the Functions 2 and 3 results. However, Function 1 had acceptable structured coefficients for all the components except conscientiousness (| r s |s > .45; Ekwonye & DeLauer, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Because the commonality between the two constructs was relatively low and most of the structured coefficients (i.e., correlation coefficients between a synthetic variable and an observed variable) were not noteworthy (| r s |s < .45; Ekwonye & DeLauer, 2019), it was difficult to interpret the Functions 2 and 3 results. However, Function 1 had acceptable structured coefficients for all the components except conscientiousness (| r s |s > .45; Ekwonye & DeLauer, 2019). Thus, the results of canonical correlation analysis should be interpreted based on Function 1…”
Section: Resultsmentioning
confidence: 99%
“…The healthy interactions with the external environment forces develop a sense of well-being. Ekwonye & DeLauer (2019) add that social integration and peer connections are positively correlated to academic resiliency. As such, the whole school community develops the resilience of its students in which Franklin (2017) noted that school climate, the role of teacher-student and counselor relationships are important in the development of resilience in students while Lee (2009) notes on the role of caring and supportive adults.…”
Section: Factors Affecting Academic Resiliencementioning
confidence: 86%
“…There are several academic factors associated with resilience as well. Chow, Tang, Chan, Sit & Choi (2018) found that resilience was a significant predictor of well-being while hope (Botor, 2019), self-efficacy (Cassidy, 2015), optimism (Molinero, Zayas, González & Guil, 2018), peer connections and spirituality (Ekwonye & DeLauer, 2019) significantly predict resilience. As resilient students interact with the environment (Zautra, 2009), the role of school, teachers and counselors are primarily important (Franklin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of college students not only consider themselves spiritual but seek out opportunities to help them grow spiritually (Kuh & Gonyea, 2006;Astin et al, 2004). Spirituality impacts student outcomes such as mental health (Dhama et al, 2017;Deb, McGirr, & Sun, 2016), academic resilience, (Ekwonye & DeLauer, 2019), and healthy behaviors (Hooker, Masters, & Carey, 2014;Mehri, Solhi, Garmaroudi, Nadrian, & Sighaldeh, 2016). A review of 20 research studies found a positive association between relational spirituality and quality of life across different age groups, including young adults (Counted, Possamai, & Meade, 2018).…”
Section: Introductionmentioning
confidence: 99%